Phenotypic Peculiarities of Pathogenic Burkholderia Mutants Resistant to Fluoroquinolones and Cephalosporins - E. V. Kalinkina; N. P. Ageeva; O. A. Merinova; D. A. Loboiko; D. V. Viktorov; L. K. Merinova (Проблемы особо опасных инфекций, 2008)
Examined were phenotypic peculiarities of mutants of Burkholderia phylogenetically-related pathogenic species (B. pseudomallei, B. mallei, B. cepacia) resistant to fluoroquinolones and cephalosporins. It was shown that strains with PfxR (OfxR), CfzR markers acquire high multi-drug resistance to antibiotics of different classes. Strain resistance changes under blocking influence of verapamil - inhibitor of calcium membrane channels. Mutant strains differ in production of extracellular enzymes (proteases, lecithinase, lipase) and virulence.